Synthesis of oil palm empty fruit bunch (EFB) derived solid acid catalyst for esterification of waste cooking oils - Koguleshun., S.; Pua, Fei-ling; Nabihah, S.; Chia, Chin-Hua; Shamala, G. (Universiti Kebangsaan Malaysia, 2015)
Oil palm empty fruit bunch (EFB) contributes to a large quantity of lignocellulosic waste. It is an abundantly available waste biomass in Malaysia. This project was aimed to utilize the waste materials for a better benefit. EFB were used as raw material to prepare a new solid catalyst for biodiesel production. Solid acid catalyst derived from EFB was used to catalyze the esterification process in biodiesel production from waste cooking oil. Solid acid catalyst was prepared by direct impregnation with transition metal sulfides, Fe2(SO4)3. This new catalyst was used to catalyze the esterification of high free fatty acid (FFA) value oil, e.g. waste cooking oils (WCOs) as pre-treatment step prior to biodiesel production. The highest catalytic activity with 90.95% esterification rate was achieved. The catalyst can be easily separated for reuse compared to homogenous catalyst which are used in biodiesel production. EFB has the potential to be converted into useful feedstock and the derived catalyst can replace the traditional liquid acid catalyst in biodiesel production especially for high acid value content feedstock.